MARCAS: avaliação da gestão do Design em microempresas. - LAVAREDA, Marina Silva Soares (2019)
This study sought to analyze how the graphic design associated to the brand and the uses of the visual identity of microenterprises is done, given the importance of this group and its representativeness in the field of formally constituted companies. Port of company profile, has peculiarities that define as that entrepreneur who present all their savings in an enterprise that is the integral dedication. For these businesses, solving problems and customers and suppliers is a daily routine, leaving in the background, actions of planning, strategic thinking, innovation, management of the institutional brand and its representativeness in the market. Through a case study, a forum researched a survey on companies in the city of São Luis that promote design solutions, as well as two microenterprises seeking support at SEBRAE in Maranhão to develop an institutional brand. It is an exploratory research, with comparative analysis by qualitative procedures. Observe if a project of development of business projects is present in the profile of the companies and the aspect of the professionals of design is not compatible with the image of its companies.